Zeolitic imidazolate framework membranes for gas separations: current state-of-the-art, challenges, and opportunities - Abdul Hamid, Mohamad Rezi; Shean Yaw, Thomas Choong; Mohd Tohir, Mohd Zahirasri; Wan Abdul Karim Ghani, Wan Azlina; Sutrisna, Putu Doddy; Jeong, Hae-Kwon (Korean Society of Industrial Engineering Chemistry, 2021)
Advanced porous materials with uniform molecular scale apertures are highly desirable for energy related separations. Among them, zeolitic imidazolate frameworks (ZIFs) have received significant interest as separation membranes owing to their narrow apertures that can target small gases. ZIFs exhibit excellent gas transport properties, such as unprecedentedly high C3H6 permeability and remarkable C3H6/C3H8 selectivity, inaccessible by other porous inorganic materials and polymers. Deposition of ultrathin ZIFs on porous substrates to form gas-selective barriers has been a major focus in this area. There has been a significant development in the synthesis of ultrathin ZIF membranes for gas separations. In this review, we present a summary of current state-of-the-art in ZIF membrane processing and highlight unique microstructural features of the prepared membranes. Following this, we discuss level of separation performances of these advanced membranes focusing on three emerging/unsolved applications. Finally, we provide our perspectives on future research directions in the area.